The Representation of Character Education Values in the Film Sang Kiai by Rako Prijanto - Irfan Afandi; Jauhari Alwi Rois; Al Muftiyah (IAIN Batusangkar, 2026)
This study is motivated by the phenomenon of extremely easy access to videos and films through various social media platforms, which has led many people to consume various types of uneducational content that erodes their character values. The film Sang Kiai by Rako Prijanto (2013) is a must-watch for them because it provides concrete examples of character education values in everyday life. The research method used is qualitative descriptive with a library research approach. Data sources are drawn directly from the film Sang Kiai and several books related to character education theory. Scene selection in the film employs purposive sampling. By using content analysis, the researcher can easily identify dialogues, scenes, and atmospheres that display specific character values in the film, thereby yielding a comprehensive understanding and results. The focus of this study is to identify character education values in the film Sang Kiai, their representations, and their relevance to character education theory. The analysis identified 22 scene representations comprising the values of politeness (6 scenes), emotional control (3 scenes), independence (2 scenes), compassion (4 scenes), and patriotism (7 scenes). Beyond mere frequency of occurrence, these findings indicate the significance and close interconnection among these values in shaping moral messages. The values of courtesy and emotional control serve as the spiritual and moral foundation of the characters, which in turn underpin the development of independent attitudes and care for the community. It is the integration of these four values that ultimately manifests a strong sense of patriotism (as reflected in the jihad resolution). The film Sang Kiai does not merely present character values in isolation but weaves them into a holistic educational framework, making it highly relevant and comprehensive as an educational medium. Keywords: Representation, Character education, Film Sang Kiai, Rako Prijanto